(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Cloud computing is a technological advancement that focuses on the way in which we design computing systems, develop applications, and leverage existing services for building software. It is based on the concept of dynamic provisioning, which is applied not only to services, but also to compute capability, storage, networking, and Information Technology (IT) infrastructure in general. Resources are made available through the Internet and offered on a pay-per-use basis from Cloud computing vendors. Today, anyone with a credit card can subscribe to Cloud services, and deploy and configure servers for an application in hours, growing and shrinking the infrastructure serving its application according to the demand, and paying only for the time these resources have been used.This vision of computing utilities based on a service provisioning model anticipated the massive transformation of the entire computing industry in the 21st century whereby computing services will be readily available on demand, like other utility services such as water, electricity, telephone, and gas available in today’s society. Similarly, users (consumers) need to pay providers only when they access the computing services. In addition, consumers no longer need to invest heavily, or encounter difficulties in building and maintaining complex IT infrastructure.